Krisis Identitas Bangsa Yehuda dalam Kitab Daniel: Studi Kasus dan Relevansinya bagi Konseling Pastoral Masa Kini - Ndraha, Amoli (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
The identity crisis experienced by the nation of Judah during the Babylonian exile represents a profound challenge to faith and religious identity. The cultural pressure of Babylon, expressed through the changing of names, the imposition of unclean food, and the demand to worship foreign gods, threatened the continuity of the people’s covenant relationship with God. This study aims to analyze the identity crisis of the nation of Judah in the Book of Daniel and to explore its relevance for contemporary Christians who face the influence of globalization, technological advancement, social media, and secular culture. The research employs a qualitative, historical approach, using secondary data from biblical commentaries, theological journals, and scholarly articles obtained through Google Scholar. The results show that the steadfast faith of Daniel and his companions serves as a timeless model for Christians to maintain spiritual integrity amid modern pressures. Strengthening spiritual discipline, fostering faith communities, and applying pastoral counseling are essential strategies to preserve Christian identity in the age of globalization.